Random amplified polymorphic DNA (RAPD) analysis of Phytophthora infestans isolates collected in Canada during 1994 to 1996 - Mahuku, George S.; Peters, RD; Platt, HW; Daayf, F. (Wiley, 2000)
Mating type, glucose-6-phosphate isomerase (Gpi) allozyme banding patterns, response to the fungicide metalaxyl and random amplified polymorphic DNA (RAPD) markers were used to characterize genetic variability among 141 Canadian isolates of Phytophthora infestans collected between 1994 and 1996. Multiple correspondence analysis of RAPD profiles separated isolates into 21 groups that were not correlated to groups defined by mating type, Gpi allozyme banding patterns or response to metalaxyl. Population subdivision analysis showed that 97% of the total genetic variation was found among individuals within populations, compared with 3% among populations. The average similarity coefficient among isolates was 80%. No significant differences in haplotypic diversity were observed among the years under study, but levels of genetic diversity among local populations of P. infestans were high (0.76). All classes of response to the fungicide metalaxyl were observed, with 55% of isolates displaying moderate levels of insensitivity. The high level of genetic diversity detected within populations indicates that migration and sexual recombination probably play important roles in the population biology of P. infestans in Canada.